Role of Igbo Language as Indices in Curbing Modern Day Slavery - Chukwu, Benadette Chinasaokwu (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Slavery has existed in many countries of the world, and it continues to cause a lot of untold hardships to its victims. Modern day slavery manifests through forced labour, sexual exploitation, human trafficking, neocolonialism etc. These widespread problems across Igbo land and globe are still in existence despite Government efforts to curb it through the 1999 Constitution at article 34.1(b) which declares that no person shall be held in slavery and in the criminal code Act which criminalizes slavery dealing under section 369. Also National Agency for the Prohibition of Trafficking in Persons (NAPTIP), Legislation providing for the rights and protection of children in Nigeria- Child Right Act (2003), the ugly situation has been on the increase. This paper therefore, sees the use of Igbo language as a tool to curb modern day slavery in Igbo land through various agencies like the family, school and church via mass media, folktales etc. The paper further looks into the negative effects and consequences of modern day slavery in the society. The study adopts qualitative research design because it identifies and structurally analysed the use of Igbo language in curbing modern day slavery in Igbo land. The method of data collection include: primary and secondary sources. The primary sources include: introspection i.e. the researcher’s intuitive knowledge of Igbo language and culture, oral interview and observation technique while the secondary sources include: data from relevant books, journals, and internet materials. Finally, the paper gives some recommendations that can help check and contain slavery in this modern time.